Stock photos of the Medford/Somerville campus, including fall foliage shots of the President's Lawn. Photo 001 - Tobin, Joanie (Tufts Archival Research Center, 2008)
Stock photos of the Medford/Somerville campus, including fall foliage shots of the President's Lawn.